Influence of fluorination on the properties and performance of isoindigo–quaterthiophene-based polymers. Issue 14 (18th March 2016) - Hu, Huawei; Jiang, Kui; Kim, Joo-Hyun; Yang, Guofang; Li, Zhengke; Ma, Tingxuan; Lu, Guanghao; Qu, Yongquan; Ade, Harald; Yan, He
Abstract : Isoindigo–quaterthiophene-based polymers are synthesized and compared to investigate the relationship between the fluorination position and photovoltaic properties. Abstract : Here a series of isoindigo (ID) and quaterthiophene (T4)-based donor–acceptor copolymers are synthesized and compared. The polymer with fluorination on the donor unit exhibits the strongest extent of temperature-dependent aggregation, which leads to a higher hole mobility of the polymer and PSCs with efficiencies up to 7.0% without using any processing additives. Our results provide important insights into how fluorination affects the aggregation properties and performance of isoindigo-based polymers.